2004
DOI: 10.1007/s00442-004-1667-3
|View full text |Cite
|
Sign up to set email alerts
|

Unpredictable food supply modifies costs of reproduction and hampers individual optimization

Abstract: Investment into the current reproductive attempt is thought to be at the expense of survival and/or future reproduction. Individuals are therefore expected to adjust their decisions to their physiological state and predictable aspects of environmental quality. The main predictions of the individual optimization hypothesis for bird clutch sizes are: (1) an increase in the number of recruits with an increasing number of eggs in natural broods, with no corresponding impairment of parental survival or future repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 76 publications
0
42
0
3
Order By: Relevance
“…These results indicate that the cost of raising enlarged broods depends on environmental conditions during the nestling period. Likewise, in a 6‐year brood size manipulation study of collared flycatchers ( Ficedula albicollis ), nestling condition was lower in experimentally enlarged broods and this effect was more pronounced in years with less food (Török, Hegyi, Tóth, & Könczey, 2004). Collectively, these findings underscore the importance of directly evaluating relationships between indices of environmental quality and fitness‐related traits, and annual fluctuations in these indices, when assessing the implications of late breeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicate that the cost of raising enlarged broods depends on environmental conditions during the nestling period. Likewise, in a 6‐year brood size manipulation study of collared flycatchers ( Ficedula albicollis ), nestling condition was lower in experimentally enlarged broods and this effect was more pronounced in years with less food (Török, Hegyi, Tóth, & Könczey, 2004). Collectively, these findings underscore the importance of directly evaluating relationships between indices of environmental quality and fitness‐related traits, and annual fluctuations in these indices, when assessing the implications of late breeding.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we detected a cost of enlarged brood sizes in the form of nestling mortality, independent of food abundance. Although enlarged broods may produce more fledglings (Shutler et al., 2006), this relationship may be affected by food supplies, with a greater number of fledglings produced from enlarged broods in food‐rich years and a threshold in the number of fledglings produced occurring in average food years (Török et al., 2004). Nestling survival was lower at PG than SDNRA possibly due to overall lower food supplies at PG (Figure 3); however, our work and a previous study (Harriman, 2014) suggest that parents at PG are in lower body condition than parents at SDNRA, which may also account for these results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This species is ideal for long-term studies of reproductive success. It shows a preference for nestboxes, can easily be captured, and has high breeding-site fidelity (Pärt and Gustafsson 1989;Könczey et al 1992;Hegyi et al 2002) and considerable local recruitment rates (Pärt 1990;Török et al 2004). Nestboxes were checked multiple times a week throughout the nesting period, so breeding attempts were followed from nest building to fledging.…”
Section: Study Species and Field Methodsmentioning
confidence: 99%
“…Due to the unavoidable, accidental loss of a proportion of individual samples, 214 peak time had to be determined by pooling data from all trees, but this does not cause bias as 215 medians of tree-level peak dates are nearly always the same as the pooled-data peak for the 216 given plot (our unpublished data; only one plot was used in this experiment). The height of 217 the peak was highly variable (see Török et al 2004) but it showed little correlation with peak 218 timing (log transformed peak height, N = 23 years, r = -0.075, p = 0.735), and there was little 219 difference in peak height between the three experimental years (data not shown), so we did 220 not consider peak height in our analyses. Frass collection was done at several distinct 221 locations over our greater study area.…”
Section: Introduction 38mentioning
confidence: 99%